Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.17221/150/2019-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous development of early successional vegetation improves Norway spruce forest soil after clear-cutting and renewal failure: a case study at a sandy-soil site

Abstract: Clear-cutting is the most common silvicultural system. Sometimes, if the new crop is not established successfully, clearcut is left unreforested. This study focused on a site where early successional species such as silver birch (Bi) and rowan (Ro) were accompanied with Norway spruce (Sp) in 13-year-old stand from natural regeneration at 550 m of altitude at an acidic site with eastern aspect and 25% slope. We found five types of stand composition: treeless gaps, Ro-Bi, Ro-Bi-Sp, Bi-Sp and monospecific Sp. Bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The rowan share can contribute to a faster return of base cations to the soil. There are even temporary pioneer stands mixed of birch and rowan which improved both the state of organic layers and the ground vegetation composition on formerly spruce-dominated sites following storm events (Zerbe, Meiwes 2000) or regeneration failure (Špulák, Kacálek 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rowan share can contribute to a faster return of base cations to the soil. There are even temporary pioneer stands mixed of birch and rowan which improved both the state of organic layers and the ground vegetation composition on formerly spruce-dominated sites following storm events (Zerbe, Meiwes 2000) or regeneration failure (Špulák, Kacálek 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their growth strategies, fir and rowan can be either competitors or rowan can also be a nursing species for underplanted fir (Vaněk et al 2016); in this case, an early thinning is needed to release fir under the rowan canopy (Po-lách, Špulák 2022). Rowan is capable of growing in clearcuts (Zerbe, Meiwes 2000;Chládek, Novotný 2007;Špulák, Kacálek 2020) and it is also a shade-tolerant survivor in below-canopy conditions (Chládek, Novotný 2007;Van Nevel 2014;Hamberg et al 2015;De Groote et al 2018). Also, the rowan sprouts from roots when parent trees are cut (Rouvinen, Kouki 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(2022) which found that birch regeneration did not respond to changes in soil biota but was mostly driven by changes in abiotic soil properties. Birch is an early‐colonising, light‐demanding species which tends to establish on relatively bare ground soon after a disturbance (Condé et al., 2003; Špulák & Kacálek, 2020). The capacity of birch seedlings to grow on soils without or with just a few generalist microbial symbionts may give them an advantage over other species when colonising areas that have been cleared by a disturbance, such as a forest fire.…”
Section: Discussionmentioning
confidence: 99%
“…In the center of the hairgrass-dominated clear-cut (C zone), on the contrary, birch regeneration predominated. Birch being a light-demanding pioneer species with high growth energy, rapidly occupies the cut-over space and competes both with spruce seedlings and with previous-generation spruce (retained after stand removal), outgrowing and suppressing them [33,53,54]. The analysis of competition between spruce and birch occurrence evidences a clearly negative association of spruce and birch regeneration.…”
Section: Fundingmentioning
confidence: 99%